The Medicalization of Love: Response to Critics - Earp, B; Sandberg, A; Savulescu, J (Cambridge University Press, 2016)
In 2015, we published an article entitled "The Medicalization of Love," in which we argued that both good and bad consequences could be expected to follow from love's medicalization, depending on how the process unfolded. A flurry of commentaries followed; here we offer some preliminary thoughts in reply to the more substantial of the criticisms that were raised. We focus in particular on the nature of love itself as well as the role it plays (or should play) in our lives; we also touch on a number of practical issues concerning the likely effects of any plausible "real-life" love drugs and conclude with a call for careful regulation.